2011 Seventh International Conference on Natural Computation 2011
DOI: 10.1109/icnc.2011.6022180
|View full text |Cite
|
Sign up to set email alerts
|

A resting-state fMRI study of patients with HIV infection based on regional homogeneity method

Abstract: In this study, the Regional Homogeneity (ReHo) approach was used to investigate the abnormal brain areas in individuals infected with Human Immunodeficiency Virus (HIV) compared with the controls, on the resting state with fMRI. Significantly decreased brain regions were found at multiple brain locations. However, no increased brain region appeared. These detected differences provided additional imaging evidence that HIV virus could cause serious damage to the human nervous system and cognitive abnormalities c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Structural MRI has frequently shown that reduced subcortical volumes in HIV-infected individuals are related to neurocognitive impairment (Dal Pan et al 1992; Aylward et al 1993; Paul et al 2002; Ances et al 2006). The findings reported by Qui et al (2011) support our results. Specifically, Qui et al (2011) reported reduced regional homogeneity in the thalamus.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Structural MRI has frequently shown that reduced subcortical volumes in HIV-infected individuals are related to neurocognitive impairment (Dal Pan et al 1992; Aylward et al 1993; Paul et al 2002; Ances et al 2006). The findings reported by Qui et al (2011) support our results. Specifically, Qui et al (2011) reported reduced regional homogeneity in the thalamus.…”
Section: Discussionsupporting
confidence: 92%
“…The findings reported by Qui et al (2011) support our results. Specifically, Qui et al (2011) reported reduced regional homogeneity in the thalamus. Again, thalamic involvement may reflect a sub-cortical pattern commonly seen in untreated HIV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation